APLIKASI KLINIS RETIKULOSIT - Suega, Ketut (journal of internal medicine, 2010)
Reticulocytes are immature nonnucleated erythrocytes that are released from the bone marrow following enucleation ofthe normoblast. Under the in! uence of erythropoietin, committed erythroid progenitor cells divide and differentiate through aseries of stages, giving rise basophilic normoblasts, polychromatophilic normoblasts, and orthochromic normoblastsin sequence.Reticulocytes are similar to mature red blood cells, except that they retain functioning polyribosomes and continue to synthesizehemoglobin. Because the reticulocyte stage of erythroid differentiation only lasts a few days, the number of reticulocytes in theblood is a useful clinical indicator of the rate of erythropoiesis. Reticulocytes exist in the circulation for only 1 ? 2 days and signalthe marrow erythropoietic activity 3 ? 4 days after iron was actively incorporated into haemoglobin. Early changes in reticulocytecount may simply re! ect the release of immature reticulocytes from the marrow rather than the true expansion of erythropoiesis.Reticulocyte counts have once again acquired great interest and importance following the introduction of instruments that usedyes speci